2018
DOI: 10.3389/fpls.2017.02231
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Residual Herbicides for Control of Photosystem (PS) II- and 4-Hydroxyphenylpyruvate Dioxygenase (HPPD)-Inhibitor-Resistant Palmer amaranth (Amaranthus palmeri S. Watson) in Glyphosate-Resistant Maize

Abstract: A Palmer amaranth (Amaranthus palmeri S. Watson) biotype has evolved resistance to photosystem (PS) II- (atrazine) and 4-hydroxyphenylpyruvate dioxygenase (HPPD)-inhibiting herbicides (mesotrione, tembotrione, and topramezone) in maize seed production field in Nebraska, USA. The objectives of this study were to determine the effect of soil residual pre-emergence (PRE) herbicides followed by (fb) tank-mixture of residual and foliar active post-emergence (POST) herbicides on PS-II- and HPPD-inhibitor-resistant P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 52 publications
(79 reference statements)
1
25
0
Order By: Relevance
“…Most of the PRE fb POST-WR programs resulted in ≥97% control of Palmer amaranth at 28 DAPOST. Similarly, Chahal et al (2018) reported that mixing soil-residual herbicides with foliar-active POST herbicides controlled HPPD and PSII inhibitor–resistant Palmer amaranth season-long in Nebraska. Averaged across programs, PRE-only herbicide programs reduced Palmer amaranth density by 67% at 28 DAPOST compared with the nontreated control (36 plants m −2 with PRE-only programs vs. 110 plants m −2 in nontreated control; Table 4).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Most of the PRE fb POST-WR programs resulted in ≥97% control of Palmer amaranth at 28 DAPOST. Similarly, Chahal et al (2018) reported that mixing soil-residual herbicides with foliar-active POST herbicides controlled HPPD and PSII inhibitor–resistant Palmer amaranth season-long in Nebraska. Averaged across programs, PRE-only herbicide programs reduced Palmer amaranth density by 67% at 28 DAPOST compared with the nontreated control (36 plants m −2 with PRE-only programs vs. 110 plants m −2 in nontreated control; Table 4).…”
Section: Resultsmentioning
confidence: 96%
“…Whitaker et al (2010) noted that PRE fb POST/POST-WR herbicide programs are necessary for effective management of Palmer amaranth and higher soybean yield. Moreover, Chahal et al (2018) showed that inclusion of soil-residual herbicides in POST treatments increased corn yield and net economic returns. Butts et al (2016) also reported that a PRE fb POST/POST-WR herbicide strategy is an important component in integrated weed management that can effectively manage Amaranthus spp.…”
Section: Soybean Injury and Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbicide applications to manage difficult-to-control weeds should be implemented as part of a diverse integrated weed management program (Shaner 2014) and should contain multiple components, such as sequential applications of residual herbicides (Chahal et al 2018;Sarangi and Jhala 2018;Sosnoskie and Culpepper 2014;Steckel et al 2002). In addition, treatments should be planned that contain multiple effective sites of action for those species that are most likely to develop herbicide resistance (e.g., Palmer amaranth and waterhemp) as a best management practice (Norsworthy et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although PRE herbicides are important to corn production, they usually do not provide season-long control of certain weed species with wide emergence patterns, such as common waterhemp [Amaranthus tuberculatus (Moq.) J. D. Sauer] and Palmer amaranth (A. palmeri S. Watson) unless followed by a POST herbicide (Chahal et al 2018a(Chahal et al , 2018bNolte and Young 2002;Steckel et al 2002).…”
Section: Introductionmentioning
confidence: 99%